A Cross-Sectional Study Revealing the Emergence of Erythromycin-Resistant Bordetella pertussis Carrying ptxP3 Alleles in China - Wu, Xiaoying; Du, Qianqian; Li, Dongfang; Yuan, Lin; Meng, Qinghong; Fu, Zhou; Xu, Hongmei; Yao, Kaihu; Zhao, Ruiqiu (Frontiers in Microbiology, 2022)
Background: Previous limited studies have identified Bordetella pertussis (B. pertussis) isolates circulating in China possess distinct molecular features and high rates of erythromycin resistance. Their evolution and potential impact on global pertussis prevention and control are worthy of attention. Methods: The present cross-sectional study involved 311 non-duplicate and unrelated B. pertussis strains isolated from Chinese children in 2017–2019. Their antimicrobial susceptibilities were assessed using both E-test strips and Kirby-Bauer (KB) disks diffusion methods. Seven virulence-related genes (ptxA, ptxC, ptxP, prn, fim2, fim3, and tcfA2) and the A2047G mutation in the 23S rRNA gene were detected by PCR. Based on the susceptibilities and genotypes, 50 isolates were selected for multi-locus variable-number tandem-repeat analysis (MLVA) typing and whole-genome sequencing. Results: A total of 311 B. pertussis strains were isolated from children of median age 4 months (interquartile range 2–9 months). Strains carrying the ptxP1 allele were more frequent (84.9%, 264/311), always exhibited erythromycin-resistant (ER) (except for one strain), and were mainly related to ptxA1/ptxC1/prn1 alleles (99.6%, 263/264). The remaining 47 (15.1%) strains carried the ptxP3 allele, mainly harbored the ptxA1/ptxC2/prn2 alleles (93.6%, 44/47), and were sensitive to erythromycin (except for two strains). The two ER-ptxP3 isolates were first identified in China, belonged to MT27 and MT28 according to MLVA, and were classified into sub-lineage IVd by phylogenetic analysis of their genome sequences. This sub-lineage also includes many strains carrying the ptxP3 allele spreading in developed countries. For each tested antimicrobial, the susceptibilities judged by KB disks were consistent with those determined by E-test strips. Conclusion: The present results reveal that B. pertussis strains with the ptxP1-ER profile still dominate in China, and a few strains carrying ptxP3 allele have acquired the A2047G mutation in the 23S rRNA gene and the ER phenotype. Surveillance of the drug susceptibility of B. pertussis is necessary in all countries, and the KB disk method can be adopted as a screening test.